Symbol

# Calculator search results

Formula
Solve the equation
Graph
$y = - x - 3 \left ( x - 4 \right )$
$y = 4$
$x$Intercept
$\left ( 3 , 0 \right )$
$y$Intercept
$\left ( 0 , 12 \right )$
$-x-3 \left( x-4 \right) = 4$
$x = 2$
 Solve a solution to $x$
$- x \color{#FF6800}{ - } \color{#FF6800}{ 3 } \left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \right ) = 4$
 Multiply each term in parentheses by $- 3$
$- x \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 4 } \right ) = 4$
$- x - 3 x \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 4 } \right ) = 4$
 Multiply $- 3$ and $- 4$
$- x - 3 x + \color{#FF6800}{ 12 } = 4$
$\color{#FF6800}{ - } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } + 12 = 4$
 Calculate between similar terms 
$\color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ x } + 12 = 4$
$- 4 x \color{#FF6800}{ + } \color{#FF6800}{ 12 } = 4$
 Move the constant to the right side and change the sign 
$- 4 x = 4 \color{#FF6800}{ - } \color{#FF6800}{ 12 }$
$- 4 x = \color{#FF6800}{ 4 } \color{#FF6800}{ - } \color{#FF6800}{ 12 }$
 Subtract $12$ from $4$
$- 4 x = \color{#FF6800}{ - } \color{#FF6800}{ 8 }$
$\color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 8 }$
 Change the sign of both sides of the equation 
$4 x = 8$
$\color{#FF6800}{ 4 } \color{#FF6800}{ x } = \color{#FF6800}{ 8 }$
 Divide both sides by the same number 
$\color{#FF6800}{ x } = \color{#FF6800}{ 2 }$
Have you found the solution you wanted?
Try again
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture